STUDI EKSPERIMENTAL VARIASI SARINGAN UDARA KARBURATOR TERHADAP KINERJA MESIN SEPEDA MOTOR - Syaifullah, Syaifullah; Rubiono, Gatut; Bunawi, Bunawi (Virtual of Mechanical Engineering Article, 2016)
Carburator air filter is an important part in automotive fuel system. Air filter is technicallymodified to increase the performance. This research is aimed to get the effect of air filter type due to motorcycle engine performance. The research is done by experiment using Suzuki Shogun 110 cc motorcycle. Air filter is vary as no filter, standard filter and modified filter. The engine is running at  1000,  2000,  3000  and  4000  rpm.  The  rotations  are  measured  with  tachometer.  Time  of  fuel consumption is measured for 10 ml gasoline. Experiments are conducted 3 times. The data is use to  get  fuel  consumption  and  engine  efficiency.  The  research  shows  that  carburator  air  filter  has effect due to engine performance. Modified filter has better performance than standard filter and no filter.